Hydrocortisone as an adjunct to brief cognitive-behavioural therapy for specific fear: Endocrine and cognitive biomarkers as predictors of symptom improvement. (June 2021) - Steudte-Schmiedgen, Susann; Fay, Emily; Capitao, Liliana; Kirschbaum, Clemens; Reinecke, Andrea
Background: Glucocorticoid (GC) administration prior to exposure-based cognitive-behavioural therapy (CBT) has emerged as a promising approach to facilitate treatment outcome in anxiety disorders. Further components relevant for improved CBT efficacy include raised endogenous GCs and reductions in information-processing biases to threat. Aims: To investigate hydrocortisone as an adjunct to CBT for spider fear and the modulating role of threat bias change and endogenous short-term and long-term GCs for treatment response. Methods: Spider-fearful individuals were randomized to receiving either 20 mg of hydrocortisone ( n = 17) or placebo ( n = 16) one hour prior to single-session predominantly computerised exposure-based CBT. Spider fear was assessed using self-report and behavioural approach measures at baseline, 1-day and 1-month follow-up. Threat processing was assessed at baseline and 1-day follow-up. Cortisol and cortisone were analysed from hair and saliva samples at baseline. Results/outcomes: Self-report, behavioural and threat processing indices improved following CBT. Hydrocortisone augmentation resulted in greater improvement of self-report spider fear and stronger increase in speed when approaching a spider, but not on threat bias. Neither threat bias nor endogenous GCs predicted symptom change, and no interactive effects with hydrocortisone emerged. Preliminary evidence indicated higher hair cortisone as predictor of a stronger threat bias reduction. Conclusions/interpretation: Our data extend earlier findings by suggesting that GC administration boosts the success of exposure therapy for specific fear even with a low-level therapist involvement. Future studies corroborating our result of a predictive hair GC relationship with threat bias change in larger clinical samples are needed.